ATIM-45. LONG TERM FOLLOW-UP OF A PHASE I/II STUDY TESTING THE TOXICITIES AND EFFICACY OF PEMBROLIZUMAB IN COMBINATION WITH MRI-GUIDED LASER INTERSTITIAL THERMAL THERAPY (LITT) IN RECURRENT MALIGNANT GLIOMAS. (11th November 2019) - Campian, Jian; Ghiaseddin, Ashley; Rahman, Maryam; Huang, Jiayi; Ansstas, George; Kim, Albert; Leuthardt, Eric; Tran, David
Abstract: BACKGROUND: LITT was recently demonstrated to induce temporary blood-brain barrier disruption, possibly allowing bilateral trafficking of tumor neoantigens and immune cells to induce glioma-specific immune activation - a phenomenon akin to in situ tumor vaccination. We hypothesize that combining LITT with immune checkpoint inhibition will create a synergistic therapy for recurrent GBM. METHODS: The phase 1 study is a standard 3x3 design with a maximum of 18 patients with bevacizumab-naïve recurrent WHO grade 3–4 glioma. The primary endpoint is safety and toxicity of LITT plus pembrolizumab at 100, 150, or 200mg IV q3weeks. Phase 2 includes 40 patients with bevacizumab-naïve recurrent GBM, equally randomized to either pembrolizumab alone or LITT plus pembrolizumab, with progression-free survival as the primary endpoint. Serial immunophenotyping will be performed to evaluate potential positive synergy between LITT and pembrolizumab. RESULTS: Phase 1 accrual was completed with 9 patients (3 at each pembrolizumab dose level). Two had recurrent anaplastic astrocytoma and 7 recurrent GBM. There was no dose-limiting toxicity with pembrolizumab 200mg IV q3weeks. The median number of doses given per patient was 9 (range 2 to 47). Severe adverse events possibly related to the study treatment included a grade 3 rash and diarrhea in 1 patient (11%) and grade 3 pneumonitis and hypotension in another patient (11%). No grade 3/4 intracranial edema deemed related to study treatment was observed. To date, four (44%) of these patients are still alive without tumor progression. Two (22%) GBM patients have not progressed for 29 and 33 months, respectively. Two (22%) anaplastic astrocytoma patient have not progressed for 23 and 24 months, respectively. CONCLUSIONS: LITT plus pemprolizumab 200mg IV q3weeks is well tolerated in patients with recurrent high-grade glioma. Prolonged stable diseases were observed in almost half of patients treated. Phase 2 study is ongoing and will be updated.